2011
DOI: 10.4021/gr364w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Acute Pancreatitis Severity: Comparison of Prognostic Scores

Abstract: BackgroundAcute pancreatitis has a broad clinical spectrum, from mild illness to multiple organ failure and death. Prognostic scores have been developed or adapted to predict disease severity. This study aimed to compare the prognostic scores according to sensitivity and specificity, receiver operating characteristic curves and area under the curve. Statistical correlation with disease severity, length of hospital stay, mortality and complication rates.MethodsRetrospective analysis of the clinical data of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 18 publications
7
26
1
Order By: Relevance
“…Three SAP patients with organ failure had Ranson score ≥3 on admission and 17 patients had Ranson score ≥3 after 48 hours of admission, in comparison to our study [10]. Simoes et al reported that the Ranson score had a higher sensitivity of 91.2% in predicting severity, but had lesser specificity compared to this study [13]. Kim et al reported that the Ranson score had the highest accuracy based on AUC [14].…”
Section: Discussioncontrasting
confidence: 47%
“…Three SAP patients with organ failure had Ranson score ≥3 on admission and 17 patients had Ranson score ≥3 after 48 hours of admission, in comparison to our study [10]. Simoes et al reported that the Ranson score had a higher sensitivity of 91.2% in predicting severity, but had lesser specificity compared to this study [13]. Kim et al reported that the Ranson score had the highest accuracy based on AUC [14].…”
Section: Discussioncontrasting
confidence: 47%
“…The Ranson 's score was considered a major success in assessing the severity of AP and has been used for over thirty years to predict AP severity. Literature shows a cut off value of 3 for severe pancreatitis (19) .…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system i.e. CTSI has a maximum of ten points, and patients with CTSI more than 6 have higher chances of developing complications and death (19) . Lautz et al reported that in comparison to a clinical scoring system the CT severity index is more predictable for identifying children with severe pancreatitis that are at higher risk for developing serious complications (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Among these scoring systems, the Acute Physiology and Chronic Health Evaluation (APACHE) II and the bedside index for severity in acute pancreatitis (BISAP) are widely used in the clinic. Although the APACHE II scoring system is valuable in evaluating the severity of AP, the scoring process is cumbersome . The BISAP score can be assessed on the first day of admission, but the accuracy and sensitivity of prediction are not high …”
mentioning
confidence: 99%
“…Although the APACHE II scoring system is valuable in evaluating the severity of AP, the scoring process is cumbersome. 3 The BISAP score can be assessed on the first day of admission, but the accuracy and sensitivity of prediction are not high. 4 Computed tomography (CT) and magnetic resonance imaging (MRI) play important roles in evaluating the complications of AP.…”
mentioning
confidence: 99%